Synthesis and characterization of calcium oxide/polyvinyl chloride (CaO/PVC)-derived materials - Bonifacio, Nicole Blaine A.; Dizon, Clarrence Anjolo Gabrielle Z.; Lalota, Nadine Mireille M.; Ladignon, Ethel Andrea C. (Manila Department of Industrial Pharmacy, College of Pharmacy, University of the Philippines Manila, 2025)
Nanomaterials are nano–sized structures with a 1–100 nm size range that can potentially detect antibiotics through fluorescence quenching/enhancement. A potential carbon–rich material such as polyvinyl chloride (PVC) can be used as an alternative precursor for nanomaterials to mitigate the environmental and health hazards that are observed from currently used precursors in the industry. Heteroatom doping enhances the surface reactivity and fluorescence quenching/enhancement activity of nanomaterials; a potential integrant that can be used to serve as the heteroatom dopant is calcium oxide (CaO). CaO/PVC–derived material was synthesized from CaO and PVC resin through a hydrothermal dechlorination method followed by pyrolysis then hydrothermal synthesis. The synthesized material had a crystalline structure, a size of 541 nm ± 182 nm (245 – 980 nm), all of which are outside the nanomaterial size range. It has a zeta potential of – 37.68 mV ± 4.518 mV but is still prone to agglomeration at higher concentrations. Its composition includes hydroxyl, carbonates, and CaO. Evaluation of fluorescence spectra shows that the material exhibits excitation–dependent fluorescence with a maximum excitation of 320 nm and maximum emission of 410 nm. Fluorescence quenching efficiencies of CaO/PVC–derived material on select antibiotics revealed quenching effects against ceftriaxone (0.810 ± 0.021), chloramphenicol (0.422 ± 0.095), streptomycin (0.189 ± 0.083), and tetracycline (0.329 ± 0.084) while enhancing effects against amoxicillin (– 1.987 ± 1.806), ciprofloxacin (–2.579 ± 0.274), and sulfamethoxazole (–0.088 ± 0.322).
Thesis (Bachelor of Science in Pharmaceutical Sciences)--University of the Philippines Manila, July 2025
Keywords: Calcium oxide -- Composite materials -- Synthesis and characterization; Polyvinyl chloride -- Hybrid composites -- Materials science; Composite materials -- Polymers and oxides -- Characterization techniques; Nanomaterial; PVC waste; hydrothermal synthesis; hydrothermal carbonization